Ta’ṡīr al-Ta’līm al-Kamūmī ‘alā Istī’āb al-Mufradāt al-Lugah al-‘Arabiyyah ladā al-Talāmīż Madrasah al-Ibtidāiyyah - Fuzielestari, Syarifah Rizcy; Wahyudi, Hakmi; Agustiar, Agustiar; Hidayat, Hakmi (Study Program of Arabic Language Teaching, 2024)
Learning a foreign language, especially Arabic, will certainly face problems. Among these problems is the students feeling bored and less enthusiastic about teaching and learning activities. It is because of many factors, such as the lack of learning media that teachers use. Arabic vocabulary is very important to learning the Arabic language. Based on the description, the researchers wanted to test an Arabic learning model. I used to model quantum teaching in Arabic vocabulary at Bunayya Grade School Pekanbaru. In this study, the problems are formulated as follows: 1) Is the use of quantum teaching in Arabic vocabulary at Bunayya Grade School Pekanbaru influenced? The purpose of this study is 1) to know the influence of using quantum teaching in Arabic vocabulary at Bunayya Grade School Pekanbaru. In the writing of this research, the researcher uses a quantitative research approach with the types of research experiments to achieve the purpose above. Data collection techniques used are observation and testing. The data were analyzed using descriptive calculations, explaining or exposing data collected in detail, as for the results of the research (1) the influence of using quantum teaching in Arabic vocabulary at Bunayya Grade School Pekanbaru. These results obtained from observation in experimental classes were quite high, 100%. The Arabic vocabulary effectively uses quantum teaching at Bunayya Grade School Pekanbaru. The average result of the experimental class is 57%, based on the N-Gain score. Calculation of T-count that is greater than the t-value of 4,836 t-tables with level 2,5% = 2,048 and value level 5% = 1,701 meant that Ho is rejected and Ha is accepted. In conclusion, using quantum teaching in Arabic vocabulary at Bunayya Grade School Pekanbaru has an influence.